Efficacy and Safety of Vonoprazan-Tetracycline Dual Therapy Versus Bismuth-Containing Quadruple Therapy for Helicobacter pylori Eradication: A Systematic Review and Meta-analysis - Amna Amir Jalal; Syeda Samia Fatima; Abdul Wasio; Rohma Zubairi; Sundus Malik; Rutaba Darooj; Sameer Mehmood; Baneen Javed Arain; Ayesha Ashar; Ayesha Arif; Syed Ibad Hussain (Annals of Pharmacotherapy, 2026)
Objective: To compare the efficacy and safety of 14-day vonoprazan-tetracycline (VT) dual therapy versus bismuth-containing quadruple therapy (BQT) for Helicobacter pylori eradication. Data Sources: PubMed/MEDLINE, Scopus, Cochrane Library, and Google Scholar were systematically searched from database inception through July 1, 2026, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Search terms included combinations of “ Helicobacter pylori ,” “vonoprazan,” “tetracycline,” “dual therapy,” “bismuth quadruple therapy,” “eradication,” and “randomized controlled trial (RCT).” Study Selection and Data Extraction: Eligible studies were RCTs comparing 14-day VT dual therapy with BQT in adults with confirmed H pylori infection. Two reviewers independently screened studies, extracted data, and assessed risk of bias. Random-effects meta-analyses were performed using pooled risk ratios (RRs) with 95% confidence intervals (CIs), and certainty of evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework. Data Synthesis: Three RCTs involving 1050 participants were included. Vonoprazan-tetracycline dual therapy achieved eradication rates comparable to BQT in intention-to-treat (RR = 1.00, 95% CI, 0.93-1.07), per-protocol (RR = 0.97, 95% CI, 0.93-1.01), and modified intention-to-treat analyses (RR = 1.01, 95% CI, 0.97-1.06). Vonoprazan-tetracycline significantly reduced total adverse events (TAEs) (RR = 0.31, 95% CI, 0.21-0.45), treatment discontinuation due to adverse events (RR = 0.12, 95% CI, 0.02-0.87), nausea (RR = 0.17, 95% CI, 0.08-0.35), and diarrhea (RR = 0.22, 95% CI, 0.08-0.67). The GRADE assessment demonstrated moderate-certainty evidence for efficacy outcomes and high-certainty evidence for most safety outcomes. Relevance to Patient Care and Clinical Practice: Vonoprazan-tetracycline dual therapy offers a simplified, penicillin-sparing regimen with eradication efficacy comparable to BQT and substantially improved tolerability. These findings support VT as a clinically relevant alternative for patients in whom treatment adherence, adverse effects, or penicillin avoidance are important considerations. Conclusions: Vonoprazan-tetracycline dual therapy provides eradication efficacy comparable to BQT while offering a significantly improved safety profile. Larger multinational RCTs are needed to confirm these findings and further define its role in first-line H pylori eradication.